2016
DOI: 10.1073/pnas.1607855113
|View full text |Cite
|
Sign up to set email alerts
|

Binding of phosphatidic acid by NsD7 mediates the formation of helical defensin–lipid oligomeric assemblies and membrane permeabilization

Abstract: Defensins are cationic antimicrobial peptides that serve as important components of host innate immune defenses, often by targeting cell membranes of pathogens. Oligomerization of defensins has been linked to their antimicrobial activity; however, the molecular basis underpinning this process remains largely unclear. Here we show that the plant defensin NsD7 targets the phospholipid phosphatidic acid (PA) to form oligomeric complexes that permeabilize PA-containing membranes. The crystal structure of the NsD7–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 21 publications
3
72
0
1
Order By: Relevance
“…S1). We recently showed that NsD7 also forms oligomeric fibrils when binding PA , however, the resultant oligomers adopt a radically different topology compared to the previously determined NaD1–PIP 2 complex . The NsD7–PA oligomer formed a double helical topology that extended throughout the crystal and featured two distinct lipid binding sites per NsD7 dimer compared to only a single site for the previously determined NaD1–PIP 2 complex.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…S1). We recently showed that NsD7 also forms oligomeric fibrils when binding PA , however, the resultant oligomers adopt a radically different topology compared to the previously determined NaD1–PIP 2 complex . The NsD7–PA oligomer formed a double helical topology that extended throughout the crystal and featured two distinct lipid binding sites per NsD7 dimer compared to only a single site for the previously determined NaD1–PIP 2 complex.…”
mentioning
confidence: 77%
“…The NsD7–PA oligomer formed a double helical topology that extended throughout the crystal and featured two distinct lipid binding sites per NsD7 dimer compared to only a single site for the previously determined NaD1–PIP 2 complex. Structure‐guided mutagenesis revealed that the novel phospholipid site not previously observed in NaD1 was critical for NsD7–PA oligomer formation as well as for fungal cell killing , demonstrating that despite their small size, defensins harbor considerable flexibility in their modes of engagement with phospholipids.…”
mentioning
confidence: 84%
“…According to the current view, such motif does not exist; PA effectors use cationic and/or surface exposed hydrophobic residues for binding to PA . Indeed, in the structures of PA‐binding proteins and peptides obtained using X‐ray crystallography and NMR , the binding of positively charged and hydrophobic residues to PA was often observed.…”
Section: Chemical Properties Of Pamentioning
confidence: 97%
“…In the studies of PA–protein interactions, various assays were used. In some of these assays, lipids were immobilized on nitrocellulose filter , coupled to the beads , or organized into liposomes . These assays are well discussed in Refs .…”
Section: Chemical Properties Of Pamentioning
confidence: 99%
“…2). Although highly unusual and unexpected, such a stoichiometric lipoprotein complex was also seen in a defensin-lipid oligomeric assembly [32]. While previously it had been assumed that the subunit-subunit interfaces forming this polymer consisted of hydrophobic α-helices from one subunit packed against hydrophobic α-helices from another subunit, it is now clear that these helix-helix interactions are actually mediated in part by the hydrophobic acyl chains of the lipids.…”
Section: Mating Pilimentioning
confidence: 99%